In Silico and In Vitro Characterization of Bacillus velezensis P45: Screening for a Novel Probiotic Candidate - Carolini Esmeriz da Rosa; Cristian Mauricio Barreto Pinilla; Luiza Dalpiccoli Toss; Adriano Brandelli (Foods)
Spore-forming Bacilli have been explored due to their potential biotechnological features and applications in human health and functional food research. This study focuses on the genetic and phenotypical characterization of the functional probiotic properties of Bacillus velezensis P45, a strain isolated from fish intestines. B. velezensis P45 exhibited antimicrobial activity against Gram-positive and Gram-negative pathogens and demonstrated strong autoaggregation and biofilm formation properties in vitro. The strain also showed tolerance to gastrointestinal conditions and ability to metabolize and adhere to mucin. In silico analysis confirmed the absence of virulence factors and antibiotic resistance genes, reinforcing its safety as a probiotic candidate. Genome mining revealed the presence of genes related to adhesion, such as fibronectin-binding protein and enolases, and for the synthesis of secondary metabolites, including the antimicrobial lipopeptides fengycin, surfactin, and bacillibactin. In addition, phylogenetic comparison using the yloA (rqcH) gene associated with gut adhesion clustered strain P45 with other probiotic Bacillus and B. velezensis strains, while separating it from pathogenic bacteria. Thus, the strain B. velezensis P45 could be a valuable candidate as a probiotic due to its functional properties and safety.